Income capability and child care - Hilde Bojer (University of Oslo, Department of Economics, 2006)
This paper has a twofold purpose. It argues firstly, that analysis of income distribution should be a part of the capability approach. Secondly, it argues that the capability approach is a good theoretical foundation for analysis of income distribution. The capability approach to human advantage has not hitherto been applied in mainstream analysis of income and wealth. The paper argues, on the one hand, that the capability approach needs to include a measure of access to economic goods; on the other hand that a capabilitydefinition of income avoids some problems inherent in the traditional, welfarist approach. A modified full income is proposed as a measure of income capability. Modified full income is Beckerian full income corrected for interalia constraints on time. Time needed to care for children (and other dependants) is a constraint on available time. The capability approach will seek to compute the cost of children (and other special needs) by identifying moral and legal constraints on time and other resources through open democratic discussion rather than econometric estimation.
Keywords: D31; D63; I31; 330; Income Distribution; Capability Approach; Cost of Children; Einkommensverteilung; Haushaltseinkommen; Kinder; Kosten